SEISMIC HAZARD ANALYSIS AND AMPLIFICATION FOR LIQUEFACTION CHARACTERIZATION ON VOLCANIC DEPOSITS OF YOUNG MERAPI VOLCANO AT BANTUL REGENCY, YOGYAKARTA PROVINCE - WIRA BUANA, TAUFIQ
Bantul regency is one of earthquake prone area due to subduction of Indo-Australia and Eurasia crust on the south and Opak fault on the east. The morphology of this area is low land between hills on the west and the east (Bantul Graben).Bantul Graben consists of Volcanic Deposits of Young Merapi Volcano. A destroyed eartrhquake evidence on May 27th, 2006 was caused by some factors such as amplification factor and liquefaction on Volcanic Deposits of Young Merapi Volcano. In this research, three analythical methods are use to answer amplification and liquefaction phenomena. Firstly, deterministic seismic hazard analysis is use to solve a peak ground acceleration value on bedrock. The result show that peak ground acceleration on bedrock for each earthquake source 1, 2 and 3 are 0.34g, 0.15g, and 0.05g respectively. Secondly, ground response linier equivalent analysis is use to run peak ground acceleratiom on bedrock toward ground surface. The variation of peak ground acceleration on each litology and amplification factor are the results from ground response linier equivalent analysis. The results show that the value of amplification between 1.3 to 2.92 times and cause peak ground acceleration value on surface be come greater up to 0.26g to 0.71g. Thirdly, liquefaction phenomena based on cyclic stress analysis by using the result of ground response linier equivalent analysis value. Safety factor and liquefied litology layers are the result from this analysis. The result show that the worst value of safety factor against liquefaction is about 0.21 with settlement effect up to 42.79 cm. The conclusions could be made that comprises three points, i.e.: earthquake source, amplification, and liquefaction. Strike-slip earthquake source type (Opak Fault) give the higest value for peak ground acceleration on bedrock compared with subduction type and the value will decline with increasing the distance from earthquake source. The amplification average of Volcanic Deposits of Young Merapi Volcano is two times and amplification values tend comparable with sediment thickness. The amplification value of each lithology will decrease with increasing density or consistency. The amplification could triggered the liquefaction phenomena only on sandy and silty deposits. On the other hand, high density or consistency (N1(60) > 20) and clayey deposits tend not liquefied. Sand deposits will liquefy if the level of density from loose to medium (N1(60) between 5-20) with cyclic stress ratio (CSR) between 0.18 to 0.53. Meanwhile, silt deposits will liquefy if the dense of consistency from very soft to stiff (N1(60) between 3-15) with cyclic stress ratio (CSR) between 0.16 to 0.69.